Facticity in Francisco Suárez’ political philosophy: a path to another Modernity - Font Oporto, Pablo (Pensamiento. Revista de Investigación e Información Filosófica, 2018)
It is possible to sustain that Suárez’s political thinking is in transit from Middle Ages to a different Modernity. The core of this interpretation is this thesis: The motor of the Suarezian political theory is the achievement of the common good inserted in the facticity of the concrete human reality. Based on these premises, the principal elements of this theory are analysed here. Firstly, the community origin of political power, which originates from the base of the social character of human beings, created in this way by God. Secondly, the operational articulation of that power, through the absolute transfer to a ruler and the (relative) preference towards Monarchy as form of government, according to Suárez. Thirdly, the acceptance of the resistance to tyranny in certain cases and conditions. Therefore, one can understand that the flagrant contradiction between the total translatio of political power andthe simultaneous admission of resistance means to reject the first, to proclaim the last as a limit to power, and open the possibility to a model of direct democracy.